Enhancement Of Candida Rugosa Lipase Via Immobilization Onto Benzyltriethyl Ammonium Chloride-Modified Supports For The Synthesis Of Nonyl-Hexanoate - Hana Meftah Elgubbi (Universiti Sains Islam Malaysia, 2024)
Matric : 4150256(FST)